2015
DOI: 10.1111/ijn.12376
|View full text |Cite
|
Sign up to set email alerts
|

Bullying among nurses and its relationship with burnout and organizational climate

Abstract: Workplace bullying is one of the most common work-related psychological problems. Bullying costs seem higher for organizations composed of health-care workers who perform direct-contact patients-complex tasks. Only a few studies have been carried out among nurses in Italy and integrated models of bullying antecedents and consequences are particularly missing. The aim of this study was to develop a bullying model focused on the interaction between bullying and burnout in the setting of a climate-health relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 38 publications
(53 reference statements)
6
109
1
3
Order By: Relevance
“…Recent investigations were directed towards the understanding of possible interconnections between bullying and burnout, showing that bullying was positively associated with burnout among nurses [20,21]. Another recent study on nurses has indicated that workplace bullying does not affect health directly, but only indirectly, via mediation of burnout [22]. In this study, we have tried to reveal how bullying is associated with psychological distress among teachers, what effect of job strain, low social support at work, life threatening events is and how burnout is interconnected in the pathway between workplace bullying and poor mental health.…”
Section: Instrumentsmentioning
confidence: 99%
“…Recent investigations were directed towards the understanding of possible interconnections between bullying and burnout, showing that bullying was positively associated with burnout among nurses [20,21]. Another recent study on nurses has indicated that workplace bullying does not affect health directly, but only indirectly, via mediation of burnout [22]. In this study, we have tried to reveal how bullying is associated with psychological distress among teachers, what effect of job strain, low social support at work, life threatening events is and how burnout is interconnected in the pathway between workplace bullying and poor mental health.…”
Section: Instrumentsmentioning
confidence: 99%
“…BB has no direct impact on physical health and mental health. BB indirectly affects employees' health through functionality as an intermediate variable (Giorgi et al, 2016).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Nursing work is demanding and stressful, which is often associated with poor well-being (e.g., Sorgaard et al, 2010; Pisanti et al, 2011, 2015; Purcell et al, 2011; Giorgi et al, 2016). Most nurses are women (in Poland, 96%) who traditionally must reconcile professional demands with responsibilities for the family.…”
Section: Introductionmentioning
confidence: 99%